Duties of a banker towards his customers / Shamsul Bahrin Baharuddin - Baharuddin, Shamsul Bahrin (Faculty of Law, 1982)
In England, the definition of a "bank" or "banker" has caused considerable confusion as Parliament has never defined thoser terms. In Malaysia, although the terms are defined in the Banking Act, 1973 confusion however arises over what the authorities concerned it to mean since in Malaysia, whether a body is a bank or not, depends on whether or not it has been granted a banking licence from the Minister. Sheldon stated that it may either be unprofitable or undesirable to try to answer the question "What is a bank?" apart from the particular context in which it is asked. This is because different criteria may be found to apply in different cases and indeed in some contexts, a person may be a bank simply because some authorithy says he is. In Malaysia, the words 'banker' and 'bank' are used quite loosely. Quite often employees of banks are described as 'bankers'. Hart has described a bank and a banker as "a person or company carrying on the business of receiving moneys, and collecting drafts for customers subject to the obligation of honouring cheques drawn upon them from time to time by the customer to the extent of the amounts available on their current accounts.